Prácticas de enseñanza de lengua en segundo año de educación general básica en una Unidad Educativa ubicada en San Rafael Valle de los Chillos. - Escobar Vizcarra, Ana Maritza (2016)
To investigate the educational practice in the area of Language and Literature becomes necessary because Ecuador has no records on this subject, especially in the early years of Basic General Education (BGE), for this reason the development of these practices were examined by means of a case study carried out in the second year of BGE in an Educational Unit in San Rafael (Chillo’s Valley), through the ethnographic method and with the support of a field diary, observation files and semi-structured interviews to the teacher and the students, in order to collect data and information to know and present the development of these practices that are based on six variables: planning, implementation of teaching and learning, work organization, assessment strategies, teacher-student interaction, and types of academic tasks. Finally it was found that the teacher, in her educational practice reproduces behavioral character models by using the synthetic method for teaching literacy. Despite the apprentices learned to read and write, they failed to understand the texts. The tasks described in the planning are executed in a mechanical, routine and monotonous way. On the other hand, some playful activities were applied, but these were used as control mechanisms in the behavior of infants. It is noteworthy that the teacher is not a guide to their students and she does not motivate them to build their own knowledge.